The Effect of Limosilactobacillus reuteri on Social Behavior Is Independent of the Adaptive Immune System - Dooling, Sean W. (2022)
Gut microbes can modulate almost all aspects of host physiology throughout life. As a result, specific microbial interventions are attracting considerable attention as potential therapeutic strategies for treating a variety of conditions. Nonetheless, little is known about the mechanisms through which many of these microbes work. Recently, we and others have found that the commensal bacterium Limosilactobacillus reuteri (formerly Lactobacillus reuteri) reverses social deficits in several mouse models (genetic, environmental, and idiopathic) for neurodevelopmental disorders in a vagus nerve-, oxytocin-, and biopterin-dependent manner. Given that gut microbes can signal to the brain through the immune system and L. reuteri promotes wound healing via the adaptive immune response, we sought to determine whether the prosocial effect mediated by L. reuteri also depends on adaptive immunity. Here, we found that the effects of L. reuteri on social behavior and related changes in synaptic function are independent of the mature adaptive immune system. Interestingly, these findings indicate that the same microbe (L. reuteri) can affect different host phenotypes through distinct mechanisms.